Fabrication and Evaluation of a Noncompliant Molar Distalizing Appliance: Bonded Molar Distalizer - A. Sodagar; M. S. Ahmad Akhoundi; A. Rafighii; S. Arab (Frontiers in Dentistry, 2011)
Objective: Attempts to treat class II malocclusions without extraction in non-compliant patients have led to utilization of intraoral molar distalizing appliances. The purpose of this study was to investigate dental and skeletal effects of Bonded Molar Distalizer (BMD) which is a simple molar distalizing appliance. Materials and Methods: Sixteen patients (12 girls, four boys) with bilateral half-cusp class II molar relationship, erupted permanent second molars and normal or vertical growth pattern were selected for bilateral distalization of maxillary molars via BMD. The screws were activated every other day, alternately. Lateral cephalograms and study models were obtained before treatment and after 11 weeks activation of the appliance. Results: Significant amounts of molar distalization, molar distal tipping and anchorage loss were observed. The mean maxillary first molar distal movement was 1.22±0.936 mm with a distal tipping of 2.97±3.74 degrees in 11 weeks. The rate of distal movement was 0.48 mm per month. Reciprocal mesial movement of the first premolars was 2.26±1.12 mm with a mesial tipping of 4.25±3.12 degrees. Maxillary incisors moved 3.55±1.46 mm and tipped 9.87±5.03 degrees mesially. Lower anterior face height (LAFH) decreased 1.28±1.36 mm. Conclusion: BMD is appropriate for distalizing maxillary molars, especially in patients with critical LAFH, although significant amounts of anchorage loss occur using this appliance.